Haloperidol increases hepatic lipid peroxidation promoted by high-fat diet in rats (Research, Society and Development, 2020)
This study aimed to evaluate the effects of the treatment with haloperidol (HAL) associated with a high-fat diet (HF) on hepatic and renal damage, intracellular magnesium (Mg2+) levels, and abdominal fat content. Young male Wistar rats were fed with high-fat diet or control diet during 48 weeks and, at the 24-week, part of animals began to be co-treated with HAL (1 mg/Kg/day intramuscularly). After 4 weeks of the drug administration, the livers and kidneys were removed for analyses. The results showed that HF diet significantly increased lipid peroxidation in the hepatic tissue of treated animals, when compared to animals treated with control diet (P